Human Rights and Conflicts in European Multicultural Societies - Ángeles SOLANES CORELLA (El Colegio de la Frontera Norte, A.C., 2013)
This paper analyzes the role of law in the management of conflicts in multicultural societies, particularly those related to migration. It discusses the dichotomy between punitive legal rules and the non-regulation by law of certain practices linked to respecting and guaranteeing human rights. For this purpose, the example is taken of the legal regulation of genital mutilation, polygamous marriage, use of the burka, the niqab, the hijab, the chador and the shyala in public spaces and the presence of religious items in schools. Th e point is to show that the law should only intervene through legislation to preserve democratic principles.